2013
DOI: 10.1037/a0033555
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling self-stigma: Are mental illness and help-seeking self-stigmas different?

Abstract: Two established but disparate lines of research exist: studies examining the self-stigma associated with mental illness and studies examining the self-stigma associated with seeking psychological help. Whereas some researchers have implicitly treated these 2 constructs as synonymous, others have made the argument that they are theoretically and empirically distinct. To help clarify this debate, we examined in the present investigation the overlap and uniqueness of the self-stigmas associated with mental illnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
219
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(242 citation statements)
references
References 64 publications
19
219
3
1
Order By: Relevance
“…This is consistent with other findings, [21, 22 23]. In a study of stigma and help seeking, Tucker et al [21] reported that stigmatizing opinions of mental illness predicted poor help seeking attitudes for a mental disorder among individuals. Similarly in a metaanalysis, Hadlaczky et al [22] & Clement et al [23] pointed out that improving knowledge of mental illness decreased their negative opinions about mental illness; in addition leading to an improvement of attitudes towards help seeking.…”
Section: Attitudes Towards Professional Psychological Help Seeking Amsupporting
confidence: 82%
“…This is consistent with other findings, [21, 22 23]. In a study of stigma and help seeking, Tucker et al [21] reported that stigmatizing opinions of mental illness predicted poor help seeking attitudes for a mental disorder among individuals. Similarly in a metaanalysis, Hadlaczky et al [22] & Clement et al [23] pointed out that improving knowledge of mental illness decreased their negative opinions about mental illness; in addition leading to an improvement of attitudes towards help seeking.…”
Section: Attitudes Towards Professional Psychological Help Seeking Amsupporting
confidence: 82%
“…Early conceptualizations, such as Link's (1987) Modified Labeling Theory, treated the stigma associated with the act of seeking help as a subset of the broader construct of mental illness stigma. However, more recent investigations have supported the independence and incremental validity of the two constructs (e.g., Ben-Porath, 2002;Tucker et al, 2013). In particular, Tucker and colleagues found that (a) a measure of the self-stigma of mental illness and a measure of the self-stigma of seeking help formed related but independent factors and (b) the measure of the self-stigma of seeking help predicted unique variance in attitudes toward seeking professional psychological help and intentions to seek professional psychological help beyond the self-stigma of mental illness.…”
Section: Self-stigma Of Seeking Helpmentioning
confidence: 99%
“…Therefore, I anticipated that stronger help-seeker stereotype endorsement, as the first step of self-stigma, would be associated with more negative attitudes toward seeking professional psychological help. Fourth, because the stigma of seeking help is closely related to, yet independent from, the stigma of mental illness (Tucker et al, 2013), I anticipated that stronger help-seeker stereotype endorsement would be positively associated with stronger mental illness stereotype endorsement.…”
Section: Convergent Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, mental health specialists may experience secondary stigma as they are often treated less positively in the professional and public society when compared to other specialists (Schulze, 2007;Verhaeghe, & Bracke, 2012). Due to this stigmatization, mental health care professionals might develop self-stigma -one associated with seeking treatment and help for themselves when needed (Corrigan, 2004;Tucker et al, 2013). The help seeking stigma "is the perception that a person who seeks psychological treatment is undesirable or socially unacceptable" (Vogel, Wade, & Haake, 2006, p. 325).…”
mentioning
confidence: 99%